P038 Comparison of Anyplex™II STI-7e v1.1 to Allplex™ CT/NG/MG/TV for the detection of STI from urine collected with UriSponge™. (14th July 2019) - Castriciano, Santina; Archenti, Anna; Biagiola, Patrizia; Pasquali, Debora; Sabelli, Cristiano; Foti, Marina
Abstract : Background: Sexual transmitted infections are playing an important role in genital infections. Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Mycoplasma genitalium (MG) and Trichomonas vaginalis (TV), have been associated to vaginal infections, cervicitis and urethritis tand complications like pelvic inflammatory diseases. Pathogens like Mycoplasma hominis (MH), Ureaplasma urealyticum (UU) and Ureaplasma parvum (UP), residing in the genital tracts, are not always associated to active infections. Seegene introduced the Allplex™ CT/NG/MG/TV (STI-4) Assay. This study objective was to compare the performance of the Anyplex™II STI-7e v1.1 (STI-7) that detects CT, NG, TV), MG, MH, UU), and UP, to the Allplex™ CT/NG/MG/TV for the detection of STI from urines. Methods: Urines collected with UriSponge™ (Copan Italia, Brescia Italy) were tested with the STI-7: UriSpone TM samples were centrifuged 5min at 2500 RPM, tubes de-capped, sponges discarded, vortexed and loaded samples on the Nimbus for nucleic acids extraction. Extracted samples were analyzed with the STI-7 on the CFX96 system. Nucleic acids from 142 urine, already defined negative and positive, were analyzed with the Allplex™ CT/NG/MG/TV on the CFX96 system. Both assays were were compared, concordant results were considered negative or positive, discordant results were retested in duplicate. Results: In the 142 urines tested with STI-7 and STI-4 assays, concordant results were detected, 29 CT, 16 NG, 11 MG positives, 29 negatives and 5 discordant results, 2 STI-7 negative/STI4 positive (1MG and 1CT) and 3 STI-7 positive/STI-4 negative (1NG, 1CT, 1TV). Results were not statistically significant (P >0.05). Anyplex II STI-7 detected 22 MH, 25 UU and 45 UP. Conclusion: In this study an excellent agreement was demonstrated by the Seegene Anyplex™II STI-7e v1.1 and by Allplex™ CT/NG/MG/TV assays for the detection of Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium (MG) from urine collected with Copan UriSponge TM. The Allplex™ CT/NG/MG/TV assays eliminate the detection of MH, UU, and UP. Disclosure: No significant relationships.